2010
DOI: 10.4155/fmc.10.203
|View full text |Cite
|
Sign up to set email alerts
|

Hiv Microbicides: State-Of-The-Art and New Perspectives on the Development of Entry Inhibitors

Abstract: Since the discovery of HIV at the beginning of the 1980s, numerous efforts have been devoted to the search of an efficient vaccine. There are at least 25 drugs available for HIV treatment, but no cure is available. The observation that therapy for HIV disease is life long and that these drugs are associated with a number of side effects underlines the need for approaches aimed at preventing rather than treating infection. Additionally, the economic burden of treatment for the HIV infection occupies an increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 140 publications
0
15
0
Order By: Relevance
“…In particular, DC-SIGN was brought to attention by the group of van Kooyk, who reported that HIV-1 targets DC-SIGN, but escapes degradation in lytic compartments, thus using DCs as a Trojan horse to invade the host organism (Geijtenbeek et al, 2000a). Inhibition of DC-SIGN is currently considered as an interesting approach for the design of new anti-infective agents (Reina et al, 2010;. The detailed molecular mechanism by which this receptor operates is not fully understood, thus effective modulators of DC-SIGN are also needed to unravel the different biological processes in which this receptor is involved.…”
Section: Dc-signmentioning
confidence: 99%
“…In particular, DC-SIGN was brought to attention by the group of van Kooyk, who reported that HIV-1 targets DC-SIGN, but escapes degradation in lytic compartments, thus using DCs as a Trojan horse to invade the host organism (Geijtenbeek et al, 2000a). Inhibition of DC-SIGN is currently considered as an interesting approach for the design of new anti-infective agents (Reina et al, 2010;. The detailed molecular mechanism by which this receptor operates is not fully understood, thus effective modulators of DC-SIGN are also needed to unravel the different biological processes in which this receptor is involved.…”
Section: Dc-signmentioning
confidence: 99%
“…It has also been shown that blocking HIV recognition by DC-SIGN effectively abrogates in trans infection. Thus, a number of groups are working to design DC-SIGN antagonists [6][7][8][9][10][11], with the goal of unveiling a new strategy to prevent sexual transmission of HIV. Effective modulators of DC-SIGN are also needed to help clarify the different biological processes in which this receptor is involved.…”
Section: Introductionmentioning
confidence: 99%
“…A handful of unnatural ligands have been described so far, both mono-and multivalent, and the subject has been recently reviewed [6,7,15].…”
Section: Introductionmentioning
confidence: 99%
“…Condoms are an excellent way to prevent infection; however, in many countries where the HIV incidence is high, men are reluctant to use them [5]. There has thus been renewed interest in new prevention strategies, and in particular, in the development of topical agents or 'microbicides' for vaginal and/ or rectal mucosal use for the purpose of preventing HIV transmission [5][6][7][8][9][10]. Unfortunately, use of microbicides for prevention of anal transmission of HIV has not been adequately addressed as yet.…”
mentioning
confidence: 97%
“…Unfortunately, use of microbicides for prevention of anal transmission of HIV has not been adequately addressed as yet. Indeed, these prevention methods are largely targeted to women, and would allow women to protect themselves in the event of condom refusal [5,10,11]. These agents have a variety of mechanisms of action, and could be formulated as a gel or cream, cervical cap or ring.…”
mentioning
confidence: 98%